2011
DOI: 10.4103/0972-0707.85789
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for periodontal ligament cell viability: An overview

Abstract: The long-term success of the reimplanted teeth is related to the maintenance of periodontal ligament (PDL) cell viability. Dental tissues are unique in comparison to most other tissues in the body due to their marked capacity for regeneration. Understanding the circumstances leading to repair and regeneration in oral tissues has been a formidable challenge. Numerous storage media have been introduced by many authors that help to maintain the PDL cell viability. To present an overview of the various available s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 36 publications
1
62
0
5
Order By: Relevance
“…In this sense, various storage media have been investigated for their ability to maintain the viability of PDL cells for as long as possible. These storage media include milk, culture media, Viaspan, Hank's Balanced Salt Solution (HBSS), Gatorade®, propolis 8,9 , soy milk 10,11 , and coconut water (CW) [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, various storage media have been investigated for their ability to maintain the viability of PDL cells for as long as possible. These storage media include milk, culture media, Viaspan, Hank's Balanced Salt Solution (HBSS), Gatorade®, propolis 8,9 , soy milk 10,11 , and coconut water (CW) [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Considering the unphysiologic media, tap water although is the most convenient medium, it causes rapid cell lysis similar to dry storage due to its hypotonicity, unphysiological pH and osmolality and microbial contamination [8,13,14] and therefore Ozan et al [15] in their study concluded that water was worse in comparison to saline [15]. Likewise saliva emphasizes similar properties as water and therefore inefficient to maintain the cellular integrity [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise saliva emphasizes similar properties as water and therefore inefficient to maintain the cellular integrity [16][17][18][19]. Even though saline solution has a physiological pH and osmolality, it does not contain the essential ions and cell nutrients for cell survival [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, in the absence of another storage medium, they may be used instead of water or saline for short periods of time. 22,26 Viaspan:…”
Section: 24mentioning
confidence: 99%